Penerapan Sistem Aplikasi Pegadaian Digital Service Dalam Memudahkan Nasabah Bertransaksi Pada PT. Pegadaian (Persero) UPC Pagelaran - Putri P., Pradhita Salsabila; Supriadi, Yoyon (LPPM IBI Kesatuan, 2022)
Pegadaian is a State-Owned Enterprise (BUMN) in Indonesia, which officially has a license to carry out financial institution activities in the form of financing in the form of channeling credit funds to the public on the basis of a pawning law. Pegadaian is a form of non-bank financial institution that has activities to finance the needs of the community, both productive and consumptive. PT. Pegadaian is now beginning to move towards the stage of transformation into a financial company. Changes made by this company by making an application to facilitate customers in the transaction. For example, PT. Pegadaian has launched an application called